Kinematical analysis on Li Ning's handspring sideways stretched sideward somersault with 1 3/4 turn in horse vaulting - Xiawen, Y. (China Sport Science and Technology, 1989)
This paper summarized and analysed the technical features and general kinematical laws of Li Ning's handspning sideways stretched sideward somersault with 1 3/4 turn (i. e. stretched Kasamatsu with 1 turn) performed by Li Ning in horse vaulting and provided the related technical parameters as well. This part performed by Li Ning had higher quality and advanced technology, which could be referenced by coaches and players in developing and improving such difficult kinds of exercises.